Analisis Kemampuan Pemecahan Masalah Matematis Siswa Dalam Menyelesaikan Soal Materi Bangun Datarsiswa Kelas IV SD 1 Burikan - Ahmad Rifqi; Siti Noor Arofah; Nuris surroyah; Fitriyah Amaliyah (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
This research aims to analyze mathematics learning, especially in number material, as well as classify students' mathematical problem solving abilities. , interviews and documentation. 12 students have no value, 5 students have moderate values and 3 students have very high scores, the questions given are 5 all description questions. In making mathematical problem solving questions we use indicators namely: 1.) Understanding new mathematical knowledge through problem solving, 2.) Designing mathematical models, 3.) implementing and adapting appropriate strategies to solve problems, 4.) completing models, 5.) monitor and reflect on the process of solving mathematical problems. Of the 5 questions, they are then assessed with an assessment rubik according to the points specified in the question grid used. The results of the assessment were categorized into 3 categories, namely high, medium category, and low category in class IV SD 1 Burikan.